Handbook of regional and urban economics. - Henderson, J. Vernon; Thisse, Jacques-Francois (Handbooks in economics, 2004)
The new Handbook of Regional and Urban Economics: Cities and Geography reviews, synthesizes and extends the key developments in urban and regional economics and their strong connection to other recent developments in modern economics. Of particular interest is the development of the new economic geography and its incorporation along with innovations in industrial organization, endogenous growth, network theory and applied econometrics into urban and regional economics. The chapters cover theoretical developments concerning the forces of agglomeration, the nature of neighborhoods and human capital externalities, the foundations of systems of cities, the development of local political institutions, regional agglomerations and regional growth. Such massive progress in understanding the theory behind urban and regional phenomenon is consistent with on-going progress in the field since the late 1960's. What is unprecedented are the developments on the empirical side: the development of a wide body of knowledge concerning the nature of urban externalities, city size distributions, urban sprawl, urban and regional trade, and regional convergence, as well as a body of knowledge on specific regions of the world-Europe, Asia and North America, both current and historical. The Handbook is a key reference piece for anyone wishing to understand the developments in the field.